2008
DOI: 10.1124/mol.108.044834
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference-Mediated Knockdown of Dynamin 2 Reduces Endocannabinoid Uptake into Neuronal dCAD Cells

Abstract: The precise mechanism by which the cellular uptake of the endocannabinoid anandamide (AEA) occurs has been the source of much debate. In the current study, we show that neuronal differentiated CAD (dCAD) cells accumulate anandamide by a process that is inhibited in a dose-dependent manner by N-(4-hydroxyphenyl)arachidonylamide (AM404). We also show that dCAD cells express functional fatty acid amide hydrolase, the enzyme primarily responsible for anandamide metabolism. Previous data from our laboratory indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 25 publications
(43 reference statements)
0
36
0
Order By: Relevance
“…Small interfering RNA (siRNA) oligonucleotides were synthesized at Bioneer Co. (Daejeon, Korea). The mRNA sequences targeted by caveolin-1, clathrin, and dynamin-2 siRNA were 5 -AGA CGA GCU GAG CGA GAA GCA -3 [18,19], 5 -AAC CUG CGG UCU GGA GUC AAC -3 [20], and 5 -GUG GAC CUG GUU AUC CAG GAG CUA A -3 [21] respectively. An unrelated (scramble) siRNA with sequence of 5 -CCU ACG CCA CCA AUU UCG U -3 was employed as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Small interfering RNA (siRNA) oligonucleotides were synthesized at Bioneer Co. (Daejeon, Korea). The mRNA sequences targeted by caveolin-1, clathrin, and dynamin-2 siRNA were 5 -AGA CGA GCU GAG CGA GAA GCA -3 [18,19], 5 -AAC CUG CGG UCU GGA GUC AAC -3 [20], and 5 -GUG GAC CUG GUU AUC CAG GAG CUA A -3 [21] respectively. An unrelated (scramble) siRNA with sequence of 5 -CCU ACG CCA CCA AUU UCG U -3 was employed as a control.…”
Section: Methodsmentioning
confidence: 99%
“…These observations are not cell-type specific because they are also present when using the neuronal CAD cells. Furthermore, down-regulation of dynamin 2, a small GTPase involved in endocytic internalization, in CAD cells leads to a decrease in the uptake of a fluorescently labeled anandamide analog and disrupts the trafficking of radiolabeled anandamide to FAAH (McFarland et al, 2008).…”
Section: Endocytosis-mediated Anandamide Uptakementioning
confidence: 99%
“…1D) (Rakhshan et al, 2000;McFarland et al, , 2008. We demonstrated that inhibition of caveolae-related endocytosis or prevention of caveolae formation led to a significant decrease in cellular AEA accumulation, thus implicating a role for these membrane microdomains in the AEA uptake process (McFarland et al, , 2008.…”
Section: Carrier-mediated Caveolae-related Endocytosismentioning
confidence: 93%
“…We demonstrated that inhibition of caveolae-related endocytosis or prevention of caveolae formation led to a significant decrease in cellular AEA accumulation, thus implicating a role for these membrane microdomains in the AEA uptake process (McFarland et al, , 2008. We propose that extracellular AEA binds a carrier protein located within caveolae, and that subsequently, caveolae-derived vesicle formation and endocytosis of the membrane-packaged endocannabinoid are induced McFarland et al, , 2008. The subsequent delivery of internalized AEA to FAAH may be a critical step in freeing the carrier protein for additional AEA transport events.…”
Section: Carrier-mediated Caveolae-related Endocytosismentioning
confidence: 97%
See 1 more Smart Citation